2013
DOI: 10.1016/j.jccw.2014.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Burn Wound Infection Using Ultraviolet Light: A Case Report

Abstract: A 9 year old girl presented to us with complaints of fever and pain in burn wounds with deteriorating health for one month. According to Lund and Broder's chart, burns spanned the posterior trunk (13%), right arm (1.5%), left arm (1.5%), and buttocks (2.5%). The wounds showed improper healing. She had previously underwent split-thickness skin grafting, using skin harvests from thighs and antimicrobial therapy with vancomycin, fluconazole and colomycin with limited clinical improvement. Analgesia was administer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…Burn patients could possibly benefit from all those factors in inflammation reduction, wound healing [ 67 ], edema control, scar maturation and improvement of muscle and soft tissue conditions. The most commonly used are paraffin therapy, hydrotherapy [ 68 ], low-frequency electrotherapy [ 69 , 70 ], medium-frequency electrotherapy, microwave therapy, shortwave therapy, air compression therapy [ 71 ], laser [ 72 , 73 ], ultraviolet therapy [ 74 ], ultrasound [ 75 ], and cold therapy [ 76 ], which can be used alone or in combination according to the specific needs and conditions of the patients.…”
Section: Implementation Of Rehabilitation Therapiesmentioning
confidence: 99%
“…Burn patients could possibly benefit from all those factors in inflammation reduction, wound healing [ 67 ], edema control, scar maturation and improvement of muscle and soft tissue conditions. The most commonly used are paraffin therapy, hydrotherapy [ 68 ], low-frequency electrotherapy [ 69 , 70 ], medium-frequency electrotherapy, microwave therapy, shortwave therapy, air compression therapy [ 71 ], laser [ 72 , 73 ], ultraviolet therapy [ 74 ], ultrasound [ 75 ], and cold therapy [ 76 ], which can be used alone or in combination according to the specific needs and conditions of the patients.…”
Section: Implementation Of Rehabilitation Therapiesmentioning
confidence: 99%
“…Vasodilatation, effective killing of pathogens, and accelerated wound closure have been highlighted [7,18,37]. In vitro studies support using UVC for wound care.…”
Section: Discussionmentioning
confidence: 99%
“…During the past few years, numerous potential therapies and approaches have been tested in wound care. Light-based therapy is a set of developing modalities in wound care, while low-level laser therapy (LLLT) and ultraviolet-C (UVC) irradiation, both have demonstrated good results and have attracted the attention of the scientific community [5,6,7]. LLLT has evolved as a rapidly growing, noninvasive physical approach to modulate various biological processes.…”
Section: Introductionmentioning
confidence: 99%
“…by damaging their DNA) particularly upon prolonged or repeated exposure, several investigations have been conducted that showed that microorganisms are overall much more susceptible to UV inactivation than mammalian cells. Therefore, it has been suggested that UV light could be used as a viable approach for infection therapy [129, 130]. UV irradiation damages microbial nucleic acids, and induces repression of the microorganism replication [131].…”
Section: Antimicrobial Light and Ultrasound-based Wound Therapymentioning
confidence: 99%